Retirement and life satisfaction among middle-aged and older adults: A piecewise growth mixture analysis - CHIA, Jonathan L. (Institutional Knowledge at Singapore Management University, 2024)
Retirement represents a significant life transition typically occurring in later adulthood, often accompanied by substantial lifestyle changes. Several theoretical frameworks suggest that these changes present both opportunities and challenges for well-being, and the extent to which individuals experience positive versus negative well-being outcomes may be influenced by various factors. To study such heterogeneity in retirement experiences, researchers have embraced person-centered methodologies. Yet, some previous studies have not robustly delineated retirement- from age-related changes in well-being, accounted for statistical uncertainties, or examined these diverse experiences outside of a Western context. These limitations preclude conclusions about the diverse experience of retirement. Using both person- and variable-centered approaches, this study examined life satisfaction trajectories before and after retirement among 532 retired middle-aged and older adults from the Singapore Life Panel. Controlling for age-related changes, latent growth mixture analysis was employed to identify retirement subgroups with varying life satisfaction trajectories. Three distinct trajectories were revealed—decreasingly satisfied, stable postretirement, and increasingly satisfied. As compared to those increasingly satisfied, decreasingly satisfied individuals tended to have lower social support, were higher on neuroticism, and had higher income. While expressed to a similar magnitude across profiles, education and religious activity also emerged as important predictors of well-being in retirement transition. Findings from the present study highlight the importance of recognizing heterogeneity in retirement experiences and opportunities for targeted interventions to support retirees’ well-being.